The characteristic of atmospheric particulate matter and the influence factors in Xiamen for air quality management - Lin, Jiali; Lin, Ying; Lin, Shuangyi; Dong, Jiaying (Frontiers in Environmental Science, 2023)
Urbanization can drive economic growth, but it may harm the quality of the urban environment if improper actions are performed. Environmental issues resulting from urbanization can negatively impact the health of city dwellers. Therefore, studying air pollutants is crucial to urban development. In this study, we focus on Xiamen and examine the distribution patterns of urban air pollutants over an extended period of time. The goal is to enhance Xiamen's air quality and bridge the research gap in long-term air quality studies specific to Xiamen. Based on monitoring data from 2014 to 2021 spanning 8 years, this study analyzed the trends in atmospheric particulate matter (PM: PM10, PM2.5) and their relationship with meteorological factors (such as wind speed: WS, temperature: T, dew point temperature: DPT, height of the cloud ceiling: HCC) and the concentrations of other pollutants (SO2, NO2, CO, and O3). The results indicated that (1) The high air quality in Xiamen with the lowest PM values observed during summer and the highest during winter; NO2 and SO2 concentrations showed similar trends to PM, while O3 and CO concentrations varied differently. (2) In general, the maximum daily PM concentration was observed in the evening and early morning, while the lowest value appeared at noon. The concentrations of PMs were positively correlated with other pollutants, while T, WS, HCC (cloud cover of more than 70%), and DPT were negatively correlated with PM concentrations. (3) There exists a relationship between concentrations of atmospheric particulate matter, atmospheric pollutants, and meteorological factors. The wind direction had varying effects on PM concentration, with PM2.5 and PM10 concentrations showing consistent trends and higher concentrations of PMs observed when winds blew from the west, southeast, and northeast. This study also provides a summary of strategies for addressing different air pollutant distribution characteristics. The purpose of this study is to analyze the distribution patterns of air pollutants in Xiamen and provide valuable insights for improving the city's air quality.